A model for prediction of cisplatin induced nephrotoxicity by kidney weight in experimental rats - Mehdi Nematbakhsh (Journal of Research in Medical Sciences, 2013)
Background: Cisplatin (cis-diamminedichloroplatinum II; CP) is used widely as an antitumor drug in clinics, but is accompanied with renal toxicity. Cisplatin induced nephrotoxicity consists of change in kidney weight, histological changes in kidney and increase in serum creatinine (Cr) and blood urea nitrogen (BUN). This study was designed to find out a model for prediction of cisplatin induced nephrotoxicity. Materials and Methods: Pathological damage score, kidney weight, BUN, and Cr of 227 rats that were involved in different projects were determined. A total of 187 rats were treated with 7 mg/kg cisplatin and sacrificed 1 week later. Results: There was a good significant correlation between normalized kidney weight and logarithmic scale of BUN and Cr. Relationship between BUN, Cr or normalized kidney weight and pathology damage score was significant. Conclusion: Normalized kidney weight and pathology damage score is a good predictor of renal function in cisplatin induced nephrotoxicity in experimental rats.